MENGENAL SISTEM PEMERINTAHAN NAGARI DI PROPINSI SUMATERA BARAT - Fauzan Zakir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Nagari is a customary law community unit in the province of West Sumatra which consists of a collection of several tribes that have certain territorial boundaries, have their own assets, have the right to regulate and manage their own household in choosing their government leaders. Nagari is also a family unit that is larger than the tribe, the nagari usually consists of approximately 4 (four) tribes, namely a large family that is related by blood from several lungs according to the mother's lineage. Historically, the nagari government is a traditional government ruled by tribal leaders who have the same authority who are incorporated in a customary density. These penghulu are assisted by the manti (smart people trusted by the penghulu), malin (clerics), and dubalang (hulubalang/security). The Nagari Government as the lowest government that replaces the Village Government is a unitary community of customary law in the area of West Sumatra Province. Consists of a collection of several tribes that have an area with certain boundaries, have their own wealth, have the right to regulate and manage their household and choose their government leaders.Keywords: Government System, Nagari, West Sumatra.